Students' Perception of English Reading Practice Using LINE Webtoon Application - Padma, Dharmasari; Male, Hendrikus; Naibaho, Lamhot (JET (Journal of English Teaching), 2025)
This study investigated students' perceptions of English reading practice using the LINE Webtoon application. The study employed a quantitative survey research design, involving 65 students of the English Language Education Study Program of Universitas Kristen Indonesia Jakarta. Data were collected in June 2023 using an online questionnaire via Google Forms distributed to the participants via WhatsApp. The questionnaire comprised 30 items designed to gauge students’ perceptions across seven indicators: access to the Webtoon application, Webtoon application features, content engagement, interest in using the application and reading comics, duration of Webtoon reading, curiosity about Webtoon, and language use within the application. The data was analyzed using descriptive statistical analysis. The findings showed that most participants had a positive perception of English reading practice through LINE Webtoon application. The factors contributing to this positive perception included the attractive and up-to-date illustrations, the engaging and unique storylines, and the flexibility of access that allows students to read anytime and anywhere.